The Effect of Locus Of Control, Self Efficacy, and E-Learning Effectiveness on Accounting Understanding - Amaliyah Amaliyah; Wiwit Irawati; Luh Nadi; Harry Barli; Alexander Raphael (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
The purpose of this study was to determine the effect of locus of control, self-efficacy, and effectiveness of e-learning on accounting understanding, with the background of the importance of the role of universities in producing competent graduates in accounting. With the Covid-19 pandemic, the learning process has changed, namely by learning through online media compared to face-to-face learning. The research population is students who graduated from the 7th semester in the accounting department at Pamulang University. The sample contains 100 data using the Slovin formula with an error margin of 10%. Data was collected through the distribution of google form questionnaires and analyzed using the combination concurrent embedded method. This research can be a reference for the academic community and also the government to produce policies and provide online-based learning services so as to produce reliable and competent graduates in the accounting field. The results show that locus of control has a significant effect on understanding Accounting, Self Efficacy, has a significant effect on accounting understanding, while the effectiveness of E-Learning has no significant effect on accounting understanding